2012
DOI: 10.1002/ejoc.201200269
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diversity of Three‐Component Reactions of N‐Benzylbenzimidazolium Salts, Isatin, and Malononitrile or Ethyl Cyanoacetate

Abstract: The three‐component reactions of N‐benzylbenzimidazolium salts, isatins, and malononitrile or ethyl cyanoacetate showed very interesting molecular diversity depending on the structures of the benzimidazolium salts. The reactions of N‐benzyl‐N′‐p‐nitrobenzylbenzimidazolium salts gave a series of zwitterionic salts in good yields. Under similar reaction conditions the reactions of N‐benzyl‐N′‐phenacylbenzimidazolium salts resulted in the unexpected products with opening of the imidazole ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Recently, we successfully found that the cycloaddition reaction of the cyclic nitrogen N -ylides with reactive 3-phenacylideneoxindoles resulted in diverse spirooxindole systems including spiro[indoline-3,1′-pyrrolo[2,1-a]isoquinolines], spiro[cyclopropane-1,3′-indolines], 3-furan-3(2 H)-ylidene)indolin-2-ones, spiro[benzo[d]pyrrolo[2,1-b]thiazole-3,3′-indolines], and complex cyclopentyl dispiroxindoles495051525354555657. We also found that three-component reactions of N -benzylbenzimidazolium salts, isatins and malononitrile or ethyl cyanoacetate gave a series of the novel zwitterionic salts and the unexpected products with opening of the imidazole ring58. These results together with the previously reports596061626364 indicated that the 1,3-dipolar cycloaddition reactions of cyclic nitrogen N -ylides with 3-methyleneoxindoles have fruitful chemistry.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…Recently, we successfully found that the cycloaddition reaction of the cyclic nitrogen N -ylides with reactive 3-phenacylideneoxindoles resulted in diverse spirooxindole systems including spiro[indoline-3,1′-pyrrolo[2,1-a]isoquinolines], spiro[cyclopropane-1,3′-indolines], 3-furan-3(2 H)-ylidene)indolin-2-ones, spiro[benzo[d]pyrrolo[2,1-b]thiazole-3,3′-indolines], and complex cyclopentyl dispiroxindoles495051525354555657. We also found that three-component reactions of N -benzylbenzimidazolium salts, isatins and malononitrile or ethyl cyanoacetate gave a series of the novel zwitterionic salts and the unexpected products with opening of the imidazole ring58. These results together with the previously reports596061626364 indicated that the 1,3-dipolar cycloaddition reactions of cyclic nitrogen N -ylides with 3-methyleneoxindoles have fruitful chemistry.…”
mentioning
confidence: 65%
“…According to our previously established reaction conditions58, an equivalent amount of N -(4-nitrobenzyl)isoquinolinium bromide, isatins and malononitrile in ethanol in the presence of triethylamine as base was stirred at room temperature overnight. The reaction was accomplished to give the expected spiro[indoline-3,2′-pyrrolo[2,1- a ]isoquinolines] 1a-1h in satisfactory yields (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[44] In recent years, we have deeply investigated 1,3-dipolar cycloaddition reactions of heterocyclic nitrogen N-ylides with 3-methyleneoxindole derivatives and found that versatile spirooxindole systems can be selectively synthesized by changing of the substrates and reaction conditions. [45][46][47][48][49][50][51][52][53][54][55] In order to further explore versatile reactivity of heterocyclic nitrogen N-ylides in 1,3-dipolar cycloadditions and provide more efficient synthetic methodology for spirocyclic compounds, …”
Section: Introductionmentioning
confidence: 99%
“…For examples, three-component reaction of N-benzylbenzimidazolium salts, isatins and malononitrile or ethyl cyanoacetate gave both of the zwitterionic salts and the unexpected products with opening of the imidazole ring. [18] The triethylamine promoted three-component reaction of isoquinolinium salts with isatins and malononitrile not only afforded spiro[indoline-3, 2'-pyrrolo[2, 1-a]isoquinolines], but also gave complex indolo[2'', 3'':2',3']pyrrolo [3', 4':4,5]pyrrolo [2, 1-a]isoquinoline and spiro [indoline-3, 8'-pyrido[2', 3':4,5]pyrrolo[2, 1-a]isoquinolines] in different conditions. [19] In order to further explore the fruitful chemistry of the heteroaromatic Nylides, herein we wish to report the 1,3-dipolar cycloaddition reaction of several quinolinium bromides with isatylidene malononitriles for the synthesis of functionalized spiro[indoline-3, 2'-pyrrolo[1, 2-a]quinolines] and the corresponding 2-(2-oxoindolin-3-ylidene)-2-(2-(dicyanomethylene)quinolin-1-yl) acetate derivatives.…”
Section: Introductionmentioning
confidence: 99%